2009
DOI: 10.1111/j.1399-5618.2009.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive impairment in bipolar disorder patients: functional implications

Abstract: Growing evidence suggests that bipolar disorder (BPD) patients experience prominent neurocognitive impairment not only during acute mood episodes (1-3) but also during euthymia (1,(4)(5)(6)(7)(8)(9)(10)(11)(12). A recent meta-analytic review of 39 studies comparing neurocognitive functioning in 948 euthymic BPD patients and 1,128 normal controls, matched for age, sex, education, and estimated premorbid IQ, found medium-to-large effect sizes (ES, as group differences ⁄ variance) for impaired attention and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(167 citation statements)
references
References 80 publications
(136 reference statements)
5
160
1
1
Order By: Relevance
“…A review of 13 studies involving a total of 813 bipolar patients found an unemployment rate of 55% (ref. 42 ). Functional outcomes in bipolar disorder are affected by various factors such as neuroticism and current level of depressive symptoms 43 as well as age, course of disorder (single episode, multiple episodes, chronic deteriorating course) insight into positive symptoms, family history of schizophrenia, and lifetime substance use disorders 44 ; other clinical and demographic factors have been described 41 .…”
Section: Cognitive Impairment and Functional Outcomesmentioning
confidence: 99%
“…A review of 13 studies involving a total of 813 bipolar patients found an unemployment rate of 55% (ref. 42 ). Functional outcomes in bipolar disorder are affected by various factors such as neuroticism and current level of depressive symptoms 43 as well as age, course of disorder (single episode, multiple episodes, chronic deteriorating course) insight into positive symptoms, family history of schizophrenia, and lifetime substance use disorders 44 ; other clinical and demographic factors have been described 41 .…”
Section: Cognitive Impairment and Functional Outcomesmentioning
confidence: 99%
“…Persistent depressive symptoms emerged as the most important predictor of poor outcome but 40% of the variance remained unaccounted for suggesting that explanatory models of the functional outcome in BD that are focused on clinical variables only do not capture the full range of possible predictors. These findings have shifted research interest towards cognitive dysfunction as the potential 'missing link' mediating psychosocial disability in BD (reviewed by Wingo et al [2009a]). …”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…3 The disorder is a significant cause of disability and suffering. 4,5 A recent international study reported that the median age at onset is 24 years for men and 27 years for women with a range of 10 to 42 years, 6 although most individuals with bipolar disorder report problems with mood and anxiety symptoms in adolescence and early adulthood.…”
Section: Epidemiology and Diagnostic Challengesmentioning
confidence: 99%